A taxonomic review of the Crypticerya species (Hemiptera: Coccoidea: Monophlebidae) of the southwestern United States and Mexico, including description of a new species from Baja California - Unruh, Corinne M. (Zootaxa, 2008)
A recent phylogenetic study of the scale insect tribe Iceryini (Hemiptera: Coccoidea: Monophlebidae) based on morphological and molecular data led to a revised generic classification, including redefinition of three genera, one of which was Crypticerya Cockerell. The new concept of Crypticerya encompasses 22 described species, all of which are found in the New World. Nine species are scattered throughout the deserts of the southwestern United States and Mexico. Here these species are redescribed and one new species, Crypticerya bursera sp.nov. is described from Baja California, Mexico. The adult female and first-instar nymph are illustrated for nine of the 10 species. A key to the adult females of the southwestern species and morphologically similar species of Crypticerya is provided.